2017
DOI: 10.1136/postgradmedj-2016-134781
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width and myocardial scar burden in coronary artery disease

Abstract: Increased RDW is an independent predictor both of myocardial scar burden and of impaired left ventricular function in subjects with coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The normal reference range for RDW in Magri's laboratory is between 11.5% and 14.5%. The authors [10,11] also supported our previous data and conclusions [5] that rheological alterations could explain an association between high RDW levels and increased total blood viscosity and whole blood viscosity (WBV) in cases of altered RBC rheological properties that result in significant changes in the microcirculation with consequent sluggish blood flow and vessel occlusions.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…The normal reference range for RDW in Magri's laboratory is between 11.5% and 14.5%. The authors [10,11] also supported our previous data and conclusions [5] that rheological alterations could explain an association between high RDW levels and increased total blood viscosity and whole blood viscosity (WBV) in cases of altered RBC rheological properties that result in significant changes in the microcirculation with consequent sluggish blood flow and vessel occlusions.…”
Section: Introductionsupporting
confidence: 77%
“…The more interesting result obtained as well as a general conclusion made by Magri et al [11] postulated that RDW was found to be an independent predictor of disease outcomes in cases of CAD together with MPV and LDL-cholesterol. In our studies [5,32], we also demonstrated interesting relationships between simultaneously increased values of RDW, MCV, WBV and simultaneously increased values of RDW, MCV, WBV and MPV in cases of chronic heroin addiction.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations